Centromedian Nucleus of the Thalamus Deep Brain Stimulation for Genetic Generalized Epilepsy: A Case Report and Review of Literature - Agashe, Shruti; Burkholder, David; Starnes, Keith; Van Gompel, Jamie J.; Lundstrom, Brian N.; Worrell, Gregory A.; Gregg, Nicholas M. (Frontiers in Human Neuroscience, 2022)
There is a paucity of treatment options for cognitively normal individuals with drug resistant genetic generalized epilepsy (GGE). Centromedian nucleus of the thalamus (CM) deep brain stimulation (DBS) may be a viable treatment for GGE. Here, we present the case of a 27-year-old cognitively normal woman with drug resistant GGE, with childhood onset. Seizure semiology are absence seizures and generalized onset tonic clonic (GTC) seizures. At baseline she had 4-8 GTC seizures per month and weekly absence seizures despite three antiseizure medications and vagus nerve stimulation. A multidisciplinary committee recommended off-label use of CM DBS in this patient. Over 12-months of CM DBS she had two GTC seizure days, which were in the setting of medication withdrawal and illness, and no GTC seizures in the last 6 months. There was no significant change in the burden of absence seizures. Presently, just two studies clearly document CM DBS in cognitively normal individuals with GGE or idiopathic generalized epilepsy (IGE) (in contrast to studies of cognitively impaired individuals with developmental and epileptic encephalopathies (DEE)). Our results suggest that CM DBS can be an effective treatment for cognitively normal individuals with GGE and underscore the need for prospective studies of CM DBS.